Exploring the Role of International Human Rights Treaties in Promoting Gender Equality and Women’s Empowerment - Ade Risna Sari; Erry Fitrya Primadhany (Westscience Press, 2023)
This research explores the role of international human rights treaties in promoting gender equality and women's empowerment in Indonesia. The study adopts a mixed-methods approach, combining qualitative and quantitative data collection techniques. The research delves into the implementation and enforcement of international human rights treaties, examining their alignment with domestic laws and policies. The study highlights the challenges and opportunities faced in advancing gender equality in Indonesia. Survey data from diverse stakeholders and insights from interviews and document analysis provide comprehensive findings. The research underscores the positive impact of international human rights treaties on gender-related policies but identifies challenges like limited resources and traditional cultural norms. The study concludes with evidence-based recommendations to enhance the influence of international human rights treaties in achieving gender equality and empowering women in Indonesia.